Obsah minerálních látek ve vybraných produktech z mořských a sladkovodních řas - Mišurcová, Ladislava; Stratilová, Ivana; Kráčmar, Stanislav (Chemické listy, 2009)
Differences in the contents of macroelements (P, Ca, Mg, K, Na), trace elements (Fe, Zn, Cu, Mn, B, Cr) and toxic elements (Pb, Cd, Hg) in food products prepared from freshwater algae or seaweed are discussed. Generally, the contents of macroelements are low. On the other hand, high contents of trace elements were observed. The order of macro- and trace elements in the products is Fe > Mn > B > Zn > K > Na > Mg > Cu > Ca > P > Cr and that of toxic elements Pb > Cd >Hg. The highest Fe contents were found in products from red seaweed Porphyra tenera, blue-green freshwater algae Spirulina pacifica and green freshwater algae Chlorella pyrenoidosa, 1833, 1480 and 1185 mg kg-1, respectively. Higher amounts of toxic elements were found in seaweed products. The highest contents of Cd and Hg were in a product from brown seaweed Wakame instant, 1.010 and 0.037 mg kg-1, respectively. The highest Pb values were in Corsican tea from red seaweed Digenes simplex, 1.509 mg kg-1 The French limits for the toxic elements were not exceeded in the investigated products.
Keywords: Spectrophotometry; minerály; Minerals; Dietary Supplements; kontaminace potravin; spektrofotometrie; potravní doplňky; Food Contamination; Eukaryota